Periostin expression correlates with pT-stage, grading and tumour size, and independently predicts cancer-specific survival in surgically treated penile squamous cell carcinomas. Issue 4 (31st January 2013) - Gunia, Sven; Jain, Anjun; Koch, Stefan; Denzinger, Stefan; Götz, Stefanie; Niessl, Nina; May, Matthias
Abstract : Aims: Overexpression of periostin, a secreted cell adhesion molecule, has been reported to enhance invasion and angiogenesis in squamous cell carcinomas (SCCs) derived from different anatomic sites. We studied the so far neglected periostin expression profiles in penile SCCs and evaluated its association with pertinent clinicopathologic variables. Methods: Paraffin-embedded tissues from 89 patients with surgically treated penile SCCs were subjected to a central histopathologic review performed by one pathologist. Then, tissue microarray technique was employed for periostin immunostaining which was evaluated by two independent raters. Kappa (κ)-statistics were used to assess interobserver variability. Spearman correlations as well as uni- and multivariable Cox proportional hazards analysis were applied to assess the association between periostin expression and clinicopathologic parameters. Mean postsurgical follow-up was 31.5 months (IQR 6–66). Results: Periostin expression was recorded in 39/89 penile SCCs (44%). K-statistics disclosed substantial interobserver agreement for epithelial and stromal staining evaluation (K-values 0.76 vs 0.83, p values <0.001). High periostin expression in either stroma or tumour epithelia showed a significant positive correlation with tumour size, histologic grade and pT-stage. In the multivariable Cox models including pT-stage, pN status, grading and the patients' age at the time of surgery, periostin expression independently predicted cancer-specific survival (CSS). Conclusions: Immunohistochemically, periostin is not infrequently expressed in penile cancer, and might become a valuable tool to independently predict CSS after surgical treatment. Further studies should clarify the so far unresolved usefulness of periostin to be employed as a possible molecular target in antineoplastic therapy in metastasised penile SCCs.